2012
DOI: 10.1007/s10803-012-1474-3
|View full text |Cite
|
Sign up to set email alerts
|

Autism and Pediatric Practice: Toward a Medical Home

Abstract: The pediatrician sees a child for 11 well child visits by their third birthday. The provision of continuous primary care supports development of trust with parents, provides opportunity for screening and surveillance of autism spectrum disorders (ASD), allows monitoring the progress of children requiring therapy, and a framework to support and educate families. Families of children with ASD are less likely to report that they receive care in a Medical Home, a practice providing coordinated, accessible, continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 46 publications
0
25
0
1
Order By: Relevance
“…Pediatricians typically see children for at least 11 well-child visits by their third birthdays and are a good source of continuous care, support, and education for families with children with ASD. 30 Specialized therapies such as OT and ST target core symptoms in self-regulation, cognition, and social-communication skills. Similarly, social skills training, a common treatment method for adolescents, can be effective for those with high-functioning autism in natural, everyday educational settings.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…Pediatricians typically see children for at least 11 well-child visits by their third birthdays and are a good source of continuous care, support, and education for families with children with ASD. 30 Specialized therapies such as OT and ST target core symptoms in self-regulation, cognition, and social-communication skills. Similarly, social skills training, a common treatment method for adolescents, can be effective for those with high-functioning autism in natural, everyday educational settings.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…[2][3][4] However, caregivers of children with ASD have reported that obtaining appropriate and timely care is often difficult and costly, 5 and many are dissatisfied with the process of obtaining care. 6,7 Caregivers of children with ASD report more unmet needs for a variety of services than caregivers of children with other emotional, developmental, or behavioral difficulties. 8,9 Caregivers of children with ASD who are from racial or ethnic minority groups experience even greater difficulty than nonminority caregivers obtaining care.…”
mentioning
confidence: 99%
“…The practice recommendations and novel findings relevant to clinical practice can support primary care practitioners in their efforts to provide a medical home for children with ASD and foster holistic and coordinated care over time. 17 Follow-up studies are needed to track the implementation of these recommendations and their impact on child and family well-being and quality of life.…”
Section: Potential Conflict Of Interestmentioning
confidence: 99%